Effects of guanidinoacetic acid on growth performance, creatine and energy metabolism, and carcass characteristics in growing-finishing pigs() - He, D T (J Anim Sci, 2018)
The aim of this study was to investigate the effects of dietary supplementation with guanidinoacetic acid (GAA) on the growth performance, creatine and energy metabolism, and carcass characteristics in growing-finishing pigs. In Exp. 1, Duroc × Landrace × Yorkshire pigs (n = 180, 33.61 ± 3.91 kg average BW) were blocked by weight and sex, and allotted to 5 treatments with 6 replicates (3 gilts and 3 barrows per replicate pen). Diets were corn-soybean meal–basal diets supplemented with 0, 300, 600, 900, and 1,200 mg/kg of GAA and fed to the pigs for 98 d. From days 1 to 98, G:F increased (linear, P < 0.05) with increasing addition of dietary GAA. Using a broken-line model, the optimum level of dietary GAA was 300 mg/kg during the overall experimental period (days 1 to 98) to maximize G:F. Hot carcass weight, carcass length, and lean percentage showed a tendency to increase (quadratic, 0.05 < P < 0.10) with increasing addition of dietary GAA. On day 98, serum GAA and liver creatine tended to increase (linear, P = 0.10, 0.07) as dietary GAA increased. In addition, serum ATP on day 98 increased linearly (linear, P < 0.01), and muscle ATP and adenosine monophosphate increased quadratically (quadratic, P = 0.05) with incremental GAA supplementation. In Exp. 2, Duroc × Landrace × Yorkshire pigs (n = 180, 53.19 ± 5.63 kg average BW) were blocked by weight and sex, and allotted to 5 treatments with 6 replicates (3 gilts and 3 barrows per replicate pen). Diets were corn-soybean meal–basal diets supplemented with 0, 150, 300, 600, and 1,200 mg/kg of GAA for 35 d. As dietary GAA increased, final BW, ADG, and G:F increased quadratically (quadratic, P < 0.01), and 300 mg/kg of GAA maximized ADG and final BW (P < 0.05).The results indicate that dietary GAA could increase the creatine and ATP load in the tissues of pigs and accordingly improve growth performance. Dietary supplementation with 300 mg/kg of GAA was suitable to maximize the growth performance of growing-finishing pigs.